Agent-based radiological emergency evacuation simulation modeling considering mitigation infrastructures. (May 2023) - Kim, Gibeom; Heo, Gyunyoung
Highlights: An integrated modeling framework for a radiological emergency based on agent-based modeling (ABM) is proposed. Emergency evacuation simulation considering mitigation infrastructures is conducted through the proposed framework. The integrated simulation enables observing various patterns of damage and recovery for evacuees. Abstract: A radiological emergency includes many elements such as evacuees, hazards, and mitigation infrastructures, and their interactions make it difficult to predict the damage and the effect of response actions. Currently, hazard assessment is conducted to assess consequences and develop a protection strategy. It contains the analysis of inventory, release, and distribution of radioactive material, dose assessment, evacuation time estimation, and so on. However, those analyses are conducted separately and based on conservative assumptions. Furthermore, the effect of mitigation infrastructures that are important for the response is not considered explicitly. In this study, an integrated radiological emergency modeling framework based on agent-based modeling (ABM) named PRISM (Platform for Radiological Emergency Integrated Simulation Model) is presented. To develop PRISM, a systemization model that identifies the elements and their interactions involved in the radiological emergency was derived through a mathematical abstraction process. To demonstrate the modeling and simulation process using PRISM, an emergency evacuation simulation considering radioactive material release and mitigation infrastructures was conducted as a case study. Besides, the sensitivity study was conducted for several model parameters from the verification perspective. Through the case study, the impact of hazard and mitigation infrastructure on evacuees was captured.